Teknologi Pembuatan Liquid Smoke Daun Kesambi sebagai Bahan Pengasapan Se’i Ikan Olahan Khas Nusa Tenggara Timur - Mamiek Mardyaningsih; Aloysius Leki; Stella Sahetapi Engel (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
The liquid smoke had been produced from raw material of kesambi leaves using pyrolysis reactor. The composition of kesambi leaves consist of 29.51% lignin, 27.62% selulosa and 15.27% hemiselulosa, and then put into pyrolysis reactor. Pyrolysing processing at 200~450oC for 5 hours and liquid smoke produced was characterized by means physicaly and proximate analyzed of pH parameter, colour, transparency, floating matters, acid, phenol and carbonil. The result of this study showed that the liquid smoke of grade 3 was generally brownish-red color, clouded, pH 2.25 and tar. For grade 2 was characterized by yellow color, slightly clouded, floating matters, pH 2.2 and grade 1 was characterized by colorless, transparent, no floating matters and pH 2.17. Proximate analyzed for liquid smoke was total phenol grade 3 was 2.57%, total acid was 13.67%, carbonil was 14.13%. On the other hand, liquid smoke grade 1 have total phenol was 0.49%, total acid was 9.78% and carbonil was 10.07%. Application of liquid smoke kesambi leaves pyrolysis results 400oC on making fish se’i meat with liquid smoke concentration of 5%, 10%, 15.20%, and 25% showed different results, both in terms of chemical components, physical and sensory properties of the fish se’i meat.